The East in the Eyes of Western Women Travellers of the 18th and 19th Centuries: Solidarity and Understanding the East - Irene Kamberidou (Proceedings (pp. 285-311) of the International Conference ‘The East in the Eyes of the West’, Nov. 26-28, 2013. Under the Patronage of the President of Kuwait University, published May 2015., 2015)
"It also may be said that in our travels we saw only the bright side of Islam. Well! That is just what we desired to see; … The fact of it is, we had heard quite enough of the dark side of Islam, so we determined to pursue our studies on the side looking to the sun … Is it right, fair, or just, to visit other people in their homes, or in their countries, wherever they dwell, and come away to decry them? No! It is not right!" argues Emilie Hayacinthe Loyson, after her travels in Oriental lands in the years 1894-1896.  Women travellers from Great Britain, France, Germany, Switzerland, Sweden, Austria and America explored, visited, worked and resided in regions of the East that were considered “proper and safe for dynamic men only” (Smith, 1887). The mammoth body of writings by women travellers of the 18th and 19th centuries, that claim to be eyewitness descriptions of the female microcosmos, provide a rich and detailed interpretation of the Orient, including a feminine version, a female gaze. European and American women identified with the so-called Other, expressed their solidarity and participated in Muslim women’s daily domestic life, customs, female social gatherings, religious celebrations and feasts. As a result, they accused male travellers- who had written about domestic manners in the East and the position of women in Islam of misinforming or mis or misleading their readers, stressing that their accounts were based on second or third-hand information, their unrestrained imagination and exotic fantasies.